Sentiment Analysis for Education and Behavior Analysis Based on Their Sentiment State - Anjali Verma,; Bappaditya Jnna, (International Journal of Scientific Research in Science and Technology, 2025)
This paper explores the role of sentiment analysis in the field of education, specifically in understanding and analysing student behaviour based on sentiment data. The study aims to leverage natural language processing (NLP) techniques to identify emotional states within educational contexts, from classroom participation to online learning environments. By implementing advanced sentiment analysis methods, this research aims to provide actionable insights into student engagement, well-being, and academic performance. The results can help educators tailor approaches to improve educational outcomes, mental health, and overall learning experiences.
Keywords: Sentiment Analysis; Education; Student Behaviour; Natural Language Processing; Student Engagement